Essentials of Pediatric Emergency Medicine Fellowship: Part 6. Issue 10 (October 2016) - Kim, In K.; Zuckerbraun, Noel; Kou, Maybelle; Vu, Tien; Levasseur, Kelly; Yen, Kenneth; Chapman, Jennifer; Doughty, Cara; McAneney, Constance; Zaveri, Pavan; Hsu, Deborah
Abstract : Abstract: This article is the sixth in a 7-part series that aims to comprehensively describe the current state and future directions of pediatric emergency medicine (PEM) fellowship training from the essential requirements to considerations for successfully administering and managing a program to the careers that may be anticipated upon program completion. This article provides a broad overview of administering and supervising a PEM fellowship program. It explores 3 topics: the principles of program administration, committee management, and recommendations for minimum time allocated for PEM fellowship program directors to administer their programs.